Regulation of gut microbiota in Alzheimer’s disease mice by silibinin and silymarin and their pharmacological implications - Shen, Liang; Liu, Lu; Li, Xin-Yu; Ji, Hong-Fang (Applied microbiology and biotechnology, 2019)
The newly reported associations between Alzheimer’s disease (AD) and gut microbiota indicate the potential of gut microbiota regulation–based therapeutic intervention for AD. Silymarin and its main active component, silibinin, are promising natural agents against AD, while their acting mechanisms remain to be explored. The present study investigated the effects of silibinin and silymarin administration on behavioral and histological manifestations, and regulation on the gut microbiota of transgenic APP/PS1 mice. First, silibinin and silymarin administration could alleviate memory deficits and reduce the amyloid plaque burden in the brain of APP/PS1 mice in comparison with controls. Second, silibinin and silymarin administration tended to decrease the microbiota diversity and exhibited regulative effect in abundances on several key bacterial species associated with AD development. This implied that gut microbiota regulation by silibinin and silymarin might be involved in their effects against AD. Further studies are warranted to fully elucidate the molecular mechanisms.